Titin-Based Cardiac Myocyte Stiffening Contributes to Early Adaptive Ventricular Remodeling After Myocardial Infarction. Issue 9 (14th October 2016) - Kötter, Sebastian; Kazmierowska, Malgorzata; Andresen, Christian; Bottermann, Katharina; Grandoch, Maria; Gorressen, Simone; Heinen, Andre; Moll, Jens M.; Scheller, Jürgen; Gödecke, Axel; Fischer, Jens W.; Schmitt, Joachim P.; et al.
Abstract : Rationale: : Myocardial infarction (MI) increases the wall stress in the viable myocardium and initiates early adaptive remodeling in the left ventricle to maintain cardiac output. Later remodeling processes include fibrotic reorganization that eventually leads to cardiac failure. Understanding the mechanisms that support cardiac function in the early phase post MI and identifying the processes that initiate transition to maladaptive remodeling are of major clinical interest. Objective: : To characterize MI-induced changes in titin-based cardiac myocyte stiffness and to elucidate the role of titin in ventricular remodeling of remote myocardium in the early phase after MI. Methods and Results: : Titin properties were analyzed in Langendorff-perfused mouse hearts after 20-minute ischemia/60-minute reperfusion (I/R), and mouse hearts that underwent ligature of the left anterior descending coronary artery for 3 or 10 days. Cardiac myocyte passive tension was significantly increased 1 hour after ischemia/reperfusion and 3 and 10 days after left anterior descending coronary artery ligature. The increased passive tension was caused by hypophosphorylation of the titin N2-B unique sequence and hyperphosphorylation of the PEVK (titin domain rich in proline, glutamate, valine, and lysine) region of titin. Blocking of interleukine-6 before left anterior descending coronary artery ligature restored titin-based myocyte tension after MI, suggesting that MI-induced titin stiffening is mediated by elevated levels of the cytokine interleukine-6. We further demonstrate that the early remodeling processes 3 days after MI involve accelerated titin turnover by the ubiquitin–proteasome system. Conclusions: : We conclude that titin-based cardiac myocyte stiffening acutely after MI is partly mediated by interleukine-6 and is an important mechanism of remote myocardium to adapt to the increased mechanical demands after myocardial injury. Abstract : Supplemental Digital Content is available in the text.